Monte Carlo Application ToolKit (MCATK). (August 2015) - Adams, Terry; Nolen, Steve; Sweezy, Jeremy; Zukaitis, Anthony; Campbell, Joann; Goorley, Tim; Greene, Simon; Aulwes, Rob
Highlights: Component-based Monte Carlo radiation transport parallel software library. Designed to build specialized software applications. Provides new functionality for existing general purpose Monte Carlo transport codes. Time-independent and time-dependent algorithms with population control. Algorithm verification and validation results are provided. Abstract: The Monte Carlo Application ToolKit (MCATK) is a component-based software library designed to build specialized applications and to provide new functionality for existing general purpose Monte Carlo radiation transport codes. We will describe MCATK and its capabilities along with presenting some verification and validations results.